The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1590/2317-1782/20152014152
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentos para avaliação de apraxia de fala infantil

Abstract: There are some tests for assessment and diagnosis of CAS. However, few studies on this topic have been conducted at the national level, as well as protocols to assess and assist in an accurate diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 15 publications
0
7
0
20
Order By: Relevance
“…Thus the consonants that compose the instrument can be perfectly articulated/uttered by 3-year-old children with typical speech development (16) . Therefore, in general, no significant performance deficits were observed in this group with regard to speech accuracy, because when the cue was again provided, the children were able to correctly utter the target.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus the consonants that compose the instrument can be perfectly articulated/uttered by 3-year-old children with typical speech development (16) . Therefore, in general, no significant performance deficits were observed in this group with regard to speech accuracy, because when the cue was again provided, the children were able to correctly utter the target.…”
Section: Discussionmentioning
confidence: 99%
“…The variables overall articulatory accuracy and consistency should be observed in children with speech sound disorders, because they may be one of the diagnostic markers for CAS (2,(8)(9)(10)(11)(12)16) . In the present research, this finding was confirmed because statistical significance was observed when these variables were compared between the different groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are articles with protocols for evaluation and review which aspects are relevant to the evaluation process of praxis 2,17,34 . Among these, we can mention: performing praxis or oral facial movement sequences of oral facial movements, parallel movements involving more than one oral facial structure, articulation of simple phonemes, joint complex phonemes and syllables, in addition to spontaneous speech.…”
Section: (Book Chapter)mentioning
confidence: 99%